Cerebral Oxygenation and Activity During Surgical Repair of Neonates With Congenital Diaphragmatic Hernia: A Center Comparison Analysis - Costerus, Sophie A.; Hendrikx, Dries; IJsselmuiden, Joen; Zahn, Katrin; Perez-Ortiz, Alba; Van Huffel, Sabine; Flint, Robert B.; Caicedo, Alexander; Wijnen, René; Wessel, Lucas; de Graaff, Jurgen C.; Tibboel, Dick; et al. (Frontiers in Pediatrics, 2021)
Background and aim: Neonatal brain monitoring is increasingly used due to reports of brain injury perioperatively. Little is known about the effect of sedatives (midazolam) and anaesthetics (sevoflurane) on cerebral oxygenation (rScO2) and cerebral activity. This study aims to determine these effects in the perioperative period. Methods: This is an observational, prospective study in two tertiary paediatric surgical centres. All neonates with a congenital diaphragmatic hernia received perioperative cerebral oxygenation and activity measurements. Patients were stratified based on intraoperatively administrated medication: the sevoflurane group (continuous sevoflurane, bolus fentanyl, bolus rocuronium) and the midazolam group (continuous midazolam, continuous fentanyl, and continuous vecuronium). Results: Intraoperatively, rScO2 was higher in the sevoflurane compared to the midazolam group (84%, IQR 77-95 vs 65%, IQR 59-76, p=<.001), fractional tissue oxygen extraction was lower (14%, IQR 5-21 vs 31%, IQR 29-40, p=<.001), the duration of hypoxia was shorter (2%, IQR 0.4-9.6 vs 38.6%, IQR 4.9-70, p=.023), and cerebral activity decreased more: slow delta: 2.16 versus 4.35 μV^2 (p=.0049), fast delta: 0.73 versus 1.37 μV^2 (p=<.001). In the first 30 min of the surgical procedure, a 3-fold increase in fast delta (10.48 to 31.22 μV^2) and a 5-fold increase in gamma (1.42 to 7.58 μV^2) were observed in the midazolam group. Conclusion: Sevoflurane-based anaesthesia resulted in increased cerebral oxygenation and decreased cerebral activity, suggesting adequate anaesthesia. Midazolam-based anaesthesia in neonates with a more severe CDH led to alarmingly low rScO2 values, below hypoxia threshold, and increased values of EEG power during the first 30 minutes of surgery. This might indicate conscious experience of pain. Integrating population-pharmacokinetic models and multimodal neuromonitoring are needed for personalized pharmacotherapy in these vulnerable patients. Trial registration: URL: https://www.trialregister.nl/trial/6972, identifier: NL6972